An Examination of the Dynamics of a Rear-inflow Jet Associated with an Idealized Mesoscale Convective System - (:unkn) unknown (My University, 2017)
This study evaluates the main controls on the descent of the rear-inflow jet (RIJ), associated with a mesoscale convective system (MCS), toward the surface. This study employs the Cloud Model 1 (CM1), release 18.3, to simulate idealized MCSs. The model has a horizontal grid spacing of 1 km with 100 vertical levels, and utilizes doubly periodic lateral boundary conditions. The Morrison double-moment explicit moisture scheme is used and Coriolis accelerations are ignored. To initiate convection, a 2 K warm bubble is applied over a limited subset of the domain. Simulations in which the magnitude of vertical wind shear is perturbed, using base-state substitution, are then considered to examine how the descent of the RIJ is impacted. It was found that for greater magnitudes of 2.5 km vertical wind shear, the RIJ associated with the simulated MCS is more elevated and stronger than with weaker wind shear over the same layer. This can be attributed to better balance between the cold pool, line-normal vertical wind shear, and RIJ. Future work includes extending the wind shear-RIJ phase space to include other magnitudes, depths, and directions of wind shear as well as comparing this implementation of base-state substitution to other applications.